1958
DOI: 10.1177/004051755802800711
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Air Pressures in the Cotton Carding Machine1

Abstract: An investigation is reported of the air pressures in the conventional cotton card, measured at strategic points with the card running idle and when processing cotton. Through the utilization of a sensitive electronic instrument capable of measuring pressures of 0.001 in. of water, both static and velocity determinations were made that have given an insight into the function of air in the card and have led to the development of a method of carding without the use of the conventional revolving flats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1959
1959
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In some tests, the air flows at a steady rate for the most part. 12,13 Therefore, we select a small periodic part of this region as the model, to reduce computation.…”
Section: Characteristics Of Cylinder-flat Regionmentioning
confidence: 99%
“…In some tests, the air flows at a steady rate for the most part. 12,13 Therefore, we select a small periodic part of this region as the model, to reduce computation.…”
Section: Characteristics Of Cylinder-flat Regionmentioning
confidence: 99%
“…Extensive aerodynamic studies [ 17] revealed that carding is accomplished through mechan--ical action and not through air action. Further studies led to the conclusion that the essential requirement for carding is that the tufts and unopened groups of fibers deposited on the cylinder by the lickerin encounter a resistant force sufficient to separate and spread the fibers over the entire area of the cylinder surface before reaching the doffer.…”
Section: Granitlar Cardmentioning
confidence: 99%
“…the differences are small within the recommended range of 60-100 granule size.Installation of the 3-NI-Ite material on the surface of the plates must be accurately controlled to prevent4 The mention of trade names does not imply their endorsement by the Department of Agriculture over similar…”
mentioning
confidence: 99%